Standardization and Qualitative Parameters for Large Scale Production of Panchamrita Parpati An Ayurvedic Drug - P K Prajapati, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Standardization and Qualitative Parameters for Large Scale Production of Panchamrita Parpati An Ayurvedic Drug